PROBLEMATIKA SERTIFIKASI WAKAF DI KECAMATAN KEPUNG KABUPATEN KEDIRI JAWA TIMUR - Furotul Hasanah; Imam Sukardi (LPPM UNHASY, 2023)
This paper explores the problematic process of waqf land certification in Kepung Sub-district, Kediri Regency. The research started with the significant number of waqf lands in Kepung Subdistrict that do not yet have legal ownership of the waqf, in the form of certificates. Educational institutions and religious institutions whose waqf has no certificate have the opportunity to become disputed land in the future. This study concludes: first, the implementation of land waqf in Kepung Sub-District, Kediri District, East Java, there are still many who hand over their waqf to the nadzir without receiving strong proof of receipt. Second, the dominant reason why people in Kepung Subdistrict do not register waqf property is that the waqf property is not registered because the heirs want to pay the waqf land tax themselves with the intention of sodaqoh and the waqf property is not registered because the cost of registering waqf property is expensive. Third, according to the review of Law Number 41 of 2004 concerning Waqf, the reasons why residents of Kepung District, Kediri Regency, East Java do not register waqf assets are not in accordance with Law Number 41 of 2004. Keywords: Certification, Land Waqf, Law Overview DAFTAR PUSTAKA Al Amin, Habibi.